(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In order to manage all academic and non-academic operations efficiently and give students abetter learning environment, including quality instruction, higher education institutions must now usethemostrecenteducationEnterpriseResourcePlanning(ERP)system.Manyactivitiesineducational institutions need a lot of time and labour, including the admissions and fee collectionprocedure, daily attendance, various administrative duties, and the process before and after exams.Different modules are included in education ERP software to efficiently manage all these tasks,which not only saves a lot of time but also ensures accuracy. The study looked at the challengescolleges in the Kanyakumari district had deploying ERP systems. For the study, a simple randomsamplingmethodisusedtoselect25collegesofartsandsciencesand25collegesofengineering.The data were analysedusing percentages andthe "t" test. The respondents suggested that thegovernmentshouldintroduceonlinescholarshipandexaminationsystemsfirstandthatproperawarenessandtrainingshould beprovidedtotheseniormanagementand professors atuniversities.